Evaluation of 3mm Vs 4mm Excision Margins in Basal Cell Carcinoma: A Multidisciplinary Study Integrating Surgical, Aesthetic and Biochemical Outcome - Sarah Zaka, Sajida Naseem, Kashif Ali, Ijaz Hussain Shah, Tariq Hussain Musadaq Asrar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Lesions of the face, head and neck area are of particular importance in the fields of plastic and reconstructive surgery, malignant ones holding a special place. The malignant cutaneous lesions can be melanomas or non-melanomas. The most common non melanotic cutaneous tumors are the Basal Cell Carcinoma and the Squamous cell carcinoma. BCC is a slow-growing, locally invasive malignant epidermal skin tumor predominantly affecting Caucasians. It’s very important to have clear margins after excision of any tumor and so is to save as much as normal healthy skin as possible in area like face which is aesthetically the most important body part. Methodology: This Randomized Control Trial was conducted in the Sheikh Zayed Medical College/Hospital Rahim Yar Khan. The study was carried out from August 2022 to February 2023. The sample size is 200 patients 100 in each group with 6.5 % margin of error, 80 % power of study taking expected percentage of margin clearance (as per operational definition) i.e., 85 % with 3 mm margin and 95 % with 4mm surgical margin in basal cell carcinoma. Non probability purposive sampling technique was used. All the data was analyzed using SPSS version 22 for Windows. Result: Out of 200 Patients 108, (54%) were males a 92 (46%) were females. Age ranged from 32 to 80 years with a mean of 59.30 years. Margin clearance was obtained in 82% patients in group one and 96% patients in group two. Chi square test showed a value of less than 0.05. Conclusion: 4mm excision margin gives a significantly greater margin clearance as compared to 3mm excision margin. Keywords: Margin Clearance, Surgical Margins, Basal Cell Carcinoma, Non Melanoma Skin Cancer.